2021
DOI: 10.3390/brainsci11091200
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Effective Connectivity in the Motor Cortex in Parkinson’s Disease

Abstract: Fast rhythms excess is a hallmark of Parkinson’s Disease (PD). To implement innovative, non-pharmacological, neurostimulation interventions to restore cortical-cortical interactions, we need to understand the neurophysiological mechanisms underlying these phenomena. Here, we investigated effective connectivity on source-level resting-state electroencephalography (EEG) signals in 15 PD participants and 10 healthy controls. First, we fitted multivariate auto-regressive models to the EEG source waveforms. Second,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Individuals with Parkinson's disease (PD) experience gait disorders that result in an increased risk of falling and a substantially decreased life quality [1]. Early gait disorders are characterized by 40 reduced gait speed and stride length and increased 41 gait variability [2, 3], suggesting that changes in walk-emission tomography (PET) findings [14][15][16]. However, a major limitation of these studies is that the participants could not walk on a pathway in a realistic environment.…”
Section: Introduction 36mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with Parkinson's disease (PD) experience gait disorders that result in an increased risk of falling and a substantially decreased life quality [1]. Early gait disorders are characterized by 40 reduced gait speed and stride length and increased 41 gait variability [2, 3], suggesting that changes in walk-emission tomography (PET) findings [14][15][16]. However, a major limitation of these studies is that the participants could not walk on a pathway in a realistic environment.…”
Section: Introduction 36mentioning
confidence: 99%
“…Prior studies have reported EC patterns in PD based on electroencephalogram (EEG), functional magnetic resonance imaging (fMRI), and positron emission tomography (PET) findings [ 14–16 ]. However, a major limitation of these studies is that the participants could not walk on a pathway in a realistic environment.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the use of EEG data is receiving increasing attention in the current literature due to the simplicity of the experimental setup and its capacity to detect rapid temporal changes in neural activity. Three papers in this Special Issue infer connectivity from EEG ( [8][9][10]). The first two papers use Granger connectivity (bivariate in Tarasi et al [9] and multivariate in Formaggio et al [8]).…”
mentioning
confidence: 99%
“…Three papers in this Special Issue infer connectivity from EEG ( [8][9][10]). The first two papers use Granger connectivity (bivariate in Tarasi et al [9] and multivariate in Formaggio et al [8]). In contrast, the last paper (Taberna et al [10]) uses a different approach based on band-limited power envelope correlations.…”
mentioning
confidence: 99%
See 1 more Smart Citation